Association Between Work-Related Stress and the Prevalence of Hypertension Among Employees of Engineering Company in 2025 - Shafira Zahara; Dewi Purnamawati (Jurnal Dunia Kesmas, 2026)
People's physical and mental health, particularly their blood pressure, may be impacted by the psychosocial disorder known as work-related stress. In 2025, this research set out to examine how engineering firm workers felt about their jobs in relation to their stress levels and the frequency with which hypertension episodes occurred. One hundred thirty-seven workers were chosen at random for a cross-sectional analytical observational research. Blood pressure was measured according to World Health Organization standards, and work-related stress was categorized as either low or high. At the 5% significance level, the data were examined using bivariate and univariate analyses using the Chi-square test. The majority of responders (62.2%) reported hypertension and high levels of stress due to their jobs. There was no statistically significant link between work-related stress and hypertension (p-value = 0.623), while the risks of acquiring hypertension were 1.41 times greater for employees with high stress levels compared to those with low stress levels. It is clear from these results that stress on the job does not play a major role in the development of hypertension in the sample group. Nonetheless, initiatives to improve and safeguard workplace health should not be abandoned.